Judicial Welfare and Legal Decision Quality in Indonesia: Normative Gaps and Reform Directions - Jonaedi Efendi; Dossy Iskandar Prasetyo (International Journal of Law Reconstruction, 2025)
This study investigates the impact of judicial welfare particularly salary structures, allowances, and institutional support on the quality of judicial decisions in Indonesia. Amid a wave of reform marked by Government Regulation Number 44 of 2024 and the 2025 salary adjustment policy, questions persist regarding whether financial improvements alone can ensure judicial independence and reasoning integrity. Using a normative legal research approach combined with doctrinal analysis and comparative jurisprudence, this paper examines salary disparities, workload imbalances, and structural gaps across judicial tiers. Findings reveal that trial-level judges continue to face excessive caseloads, inadequate access to legal resources, and limited professional development despite recent financial reforms. These structural deficiencies contribute to formalistic adjudication, reduced legal innovation, and vulnerability to ethical fatigue. The study affirms that judicial welfare reform must go beyond monetary adjustments and integrate performance-based incentives, reasoning-focused evaluation systems, and equitable institutional infrastructure. Drawing on theories of justice and motivation, the research offers a multidimensional framework for understanding how welfare structures influence judicial output. It concludes that sustained judicial quality and independence require a holistic policy response that bridges normative ideals and institutional realities.